Physical Basis of Positron Emission Tomography (Eurasian Medical Research Periodical, 2023)
The physical properties of a charged positron particle and the emission scheme are given. Two main research methods in positron emission tomography. The properties of radiopharmaceuticals used in positron emission tomography are given.